Cytolytic CD4+ and CD8+ Regulatory T-Cells and Implications for Developing Immunotherapies to Combat Graft-Versus-Host Disease - Bolivar-Wagers, Sara; Larson, Jemma H.; Jin, Sujeong; Blazar, Bruce R. (Frontiers in Immunology, 2022)
Regulatory T-cells (Treg) are critical for the maintenance of immune homeostasis and tolerance induction. While the immunosuppressive mechanisms of Treg have been extensively investigated for decades, the mechanisms responsible for Treg cytotoxicity and their therapeutic potential in regulating immune responses have been incompletely explored and exploited. Conventional cytotoxic T effector cells (Teffs) are known to be important for adaptive immune responses, particularly in the settings of viral infections and cancer. CD4+ and CD8+ Treg subsets may also share similar cytotoxic properties with conventional Teffs. Cytotoxic effector Treg (eTreg) are a heterogeneous population in the periphery that retain the capacity to suppress T-cell proliferation and activation, induce cellular apoptosis, and migrate to tissues to ensure immune homeostasis. The latter can occur through several cytolytic mechanisms, including the Granzyme/Perforin and Fas/FasL signaling pathways. This review focuses on the current knowledge and recent advances in our understanding of eTreg and their potential application in the treatment of human disease, particularly Graft-versus-Host Disease (GVHD).